The Yeast Centrin, Cdc31p, and the Interacting Protein Kinase, Kic1p, Are Required for Cell Integrity - Sullivan, Donald S. (The Rockefeller University Press, 1998)
Cdc31p is the yeast homologue of centrin, a highly conserved calcium-binding protein of the calmodulin superfamily. Previously centrins have been implicated only in microtubule-based processes. To elucidate the functions of yeast centrin, we carried out a two-hybrid screen for Cdc31p-interacting proteins and identified a novel essential protein kinase of 1,080 residues, Kic1p (kinase that interacts with Cdc31p). Kic1p is closely related to S. cerevisiae Ste20p and the p-21– activated kinases (PAKs) found in a wide variety of eukaryotic organisms. Cdc31p physically interacts with Kic1p by two criteria; Cdc31p coprecipitated with GST–Kic1p and it bound to GST–Kic1p in gel overlay assays. Furthermore, GST–Kic1p exhibited in vitro kinase activity that was CDC31-dependent. Although kic1 mutants were not defective for spindle pole body duplication, they exhibited a variety of mutant phenotypes demonstrating that Kic1p is required for cell integrity. We also found that cdc31 mutants, previously identified as defective for spindle pole body duplication, exhibited lysis and morphological defects. The cdc31 kic1 double mutants exhibited a drastic reduction in the range of permissive temperature, resulting in a severe lysis defect. We conclude that Kic1p function is dependent upon Cdc31p both in vivo and in vitro. We postulate that Cdc31p is required both for SPB duplication and for cell integrity/morphogenesis, and that the integrity/morphogenesis function is mediated through the Kic1p protein kinase.